Central safety factor and βN control on NSTX-U via beam power and plasma boundary shape modification, using TRANSP for closed loop simulations. (23rd April 2015) - Boyer, M.D.; Andre, R.; Gates, D.A.; Gerhardt, S.; Goumiri, I.R.; Menard, J.
Abstract: The high-performance operational goals of NSTX-U will require development of advanced feedback control algorithms, including control of β N and the safety factor profile. In this work, a novel approach to simultaneously controlling β N and the value of the safety factor on the magnetic axis, q 0, through manipulation of the plasma boundary shape and total beam power, is proposed. Simulations of the proposed scheme show promising results and motivate future experimental implementation and eventual integration into a more complex current profile control scheme planned to include actuation of individual beam powers, density, and loop voltage. As part of this work, a flexible framework for closed loop simulations within the high-fidelity code TRANSP was developed. The framework, used here to identify control-design-oriented models and to tune and test the proposed controller, exploits many of the predictive capabilities of TRANSP and provides a means for performing control calculations based on user-supplied data (controller matrices, target waveforms, etc). The flexible framework should enable high-fidelity testing of a variety of control algorithms, thereby reducing the amount of expensive experimental time needed to implement new control algorithms on NSTX-U and other devices.